2014
DOI: 10.1051/0004-6361/201322918
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh-Taylor instability in prominences from numerical simulations including partial ionization effects

Abstract: We study the Rayleigh-Taylor instability (RTI) at a prominence-corona transition region in a non-linear regime. Our aim is to understand how the presence of neutral atoms in the prominence plasma influences the instability growth rate, as well as the evolution of velocity, magnetic field vector, and thermodynamic parameters of turbulent drops. We perform 2.5D numerical simulations of the instability initiated by a multi-mode perturbation at the corona-prominence interface using a single-fluid magnetohydrodynam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 101 publications
3
83
0
Order By: Relevance
“…Pedersen dissipation also allows emerging magnetic field to diffuse more rapidly into the atmosphere (Leake & Arber 2006;Arber et al 2007;Leake & Linton 2013). Compared to single-fluid simulations, 2.5D simulations of prominences including partial ionization show an increase of small-scale velocities as a result of the nonlinearity of the Rayleigh-Taylor instability Khomenko et al 2014). Further details of such processes can be found in the review by Leake et al (2014), which details the impact of ion-neutral collisions and their properties in the solar chromosphere and Earth's ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Pedersen dissipation also allows emerging magnetic field to diffuse more rapidly into the atmosphere (Leake & Arber 2006;Arber et al 2007;Leake & Linton 2013). Compared to single-fluid simulations, 2.5D simulations of prominences including partial ionization show an increase of small-scale velocities as a result of the nonlinearity of the Rayleigh-Taylor instability Khomenko et al 2014). Further details of such processes can be found in the review by Leake et al (2014), which details the impact of ion-neutral collisions and their properties in the solar chromosphere and Earth's ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Dudík et al (2012) have proposed that the existence of prominence bubbles is connected to a pair of magnetic null points associated with the prominence feet, and that a separator-reconnection scenario, which is very different from the Rayleigh-Taylor hypothesis, may naturally explain the bubble and plume formation. The role of neutrals on the MRT instability was investigated (in the linear regime) by Díaz et al (2012), while Khomenko et al (2014) have considered the nonlinear regime and have found that the configuration is always unstable on small scales. The models presented by these authors are based on local models of prominences, and the effect of the corona is not included.…”
Section: Introductionmentioning
confidence: 99%
“…We need to mention here that the existence of the critical wavenumber is very much connected to the equilibrium chosen for our model. Díaz et al (2014) and Khomenko et al (2014) studied the MRT instability of a magnetic interface with the plasma only partially ionised at both sides. They found that for such an equilibrium there is no critical wavenumber meaning that perturbations with any wavenumber are unstable.…”
Section: Discussionmentioning
confidence: 99%